The mediating role of attitude and knowledge in the relationship between export/import support and global entrepreneurial mindset: Evidence from young muslims in Yogyakarta - Joko Setyono; Fetria Eka Yudiana (Faculty of Islamic Economics and Business UIN Salatiga, 2025)
Globalization and digital technology create opportunities for Muslim Generation Z in cross-border entrepreneurship, yet their understanding of export-import procedures remains limited. This study examines the mediating role of attitude, perception, and knowledge in developing a Global Entrepreneurial Mindset (GEM) among Muslim Gen Z in Yogyakarta. Using a quantitative approach with 220 respondents and PLS-SEM analysis, the results show that attitude, digital support, knowledge, policy support, and perception significantly influence GEM. Digital support positively affects attitude, opportunity awareness influences perception, and policy support affects knowledge. Attitude mediates the effect of digital support on GEM, while knowledge mediates the effect of policy support. However, perception does not mediate the relationship between opportunity awareness and GEM. These findings emphasize the strategic role of digital infrastructure, education, and supportive government policies in enhancing global entrepreneurial capacity. This study also contributes to the development of the SOR framework in global entrepreneurship.